Dangerous lessons: Rebel learning and mobilization in the international system. (September 2016) - Linebarger, Christopher
Contemporary research on the international diffusion of civil conflict privileges physical, proximity-based variables like conflict spillover and refugee flows. I argue that the international diffusion of civil strife can occur through a learning mechanism, and that this phenomenon may occur on a worldwide basis. Individuals most likely to rebel, or proto-rebels, may learn about the utility of rebellion before mobilizing and violently challenging the state. Such international learning therefore occurs during the pre-conflict process. International sources by which proto-rebels learn include active, ongoing civil wars, as well as revolutionary governments that have been founded by rebels victorious in past wars. Revolutionary governments radically shock the international system, teaching proto-rebels about the possible benefits to be gained from violently challenging the state. In order to test these assertions, I undertake empirical analyses using militant organization data that capture the year in which rebel movements first emerge, during the period 1968–2001. I then explore the spatial and temporal relationships between rebel movement emergence, civil conflict, and revolutionary regimes, using the country-year as my unit of analysis. I further examine how these relationships are attenuated by cultural and regime-type similarity. I find, in line with the literature, that active civil conflicts generally inspire rebel mobilization only in directly neighboring states, while revolutionary regimes established after rebel victories are associated with mobilization on a global basis. I conclude that proto-rebels learn and take inspiration from some global sources of information, and that significant analytical utility is to be gained by focusing on revolutionary regimes established as a result of rebel victories, as well as mobilization in the pre-conflict process.